Translation Procedures and Quality Assessment of King Charles III’s 2022 Speech by CNN Indonesia - Arina, Sitara Putri; Wijaya, Andika (Journal of Language and Literature Studies, 2026)
The quality of news translation has a significant impact on global understanding and communication, especially in an era of rapid information exchange and international media consumption. Speeches by high-profile figures, such as presidents, monarchs, and public figures, carry substantial international importance. As one of the leading news portals, CNN Indonesia plays a vital role in translating such content; however, its quality has not been thoroughly examined. This study adopts a qualitative descriptive approach using a comparative conceptual method to analyze source and target texts. It applies Vinay and Darbelnet’s (1995) translation procedure theory and Nababan, Ardiana Nuraeni, and Sumardiono’s (2012) translation quality assessment model. Findings reveal that transposition is the most frequently used procedure (66%), followed by modulation and literal translation (13%) each. Correspondingly, the overall TQA score is 2.35 out of 3, comprising accuracy at 2.19, acceptability at 2.44, and readability at 2.71. These results indicate that while the translation achieves a high level of readability and acceptability, there remains room for improvement in accuracy to fully capture the nuances of the source text. This study contributes to translation studies by demonstrating how Vinay and Darbelnet’s procedures can inform effective linguistic and cultural strategies to enhance translation accuracy and comprehension. By emphasizing the role of strategic linguistic and cultural adaptation, the study offers practical insights for improving translation quality in journalistic contexts, particularly in political and ceremonial speeches.